Clinical translation of hyperpolarized 13C pyruvate and urea MRI for simultaneous metabolic and perfusion imaging. Issue 1 (10th August 2021) - Qin, Hecong; Tang, Shuyu; Riselli, Andrew M.; Bok, Robert A.; Delos Santos, Romelyn; van Criekinge, Mark; Gordon, Jeremy W.; Aggarwal, Rahul; Chen, Rui; Goddard, Gregory; Zhang, Chunxin Tracy; Chen, Albert; et al.
Abstract : Purpose: The combined hyperpolarized (HP) 13 C pyruvate and urea MRI has provided a simultaneous assessment of glycolytic metabolism and tissue perfusion for improved cancer diagnosis and therapeutic evaluation in preclinical studies. This work aims to translate this dual‐probe HP imaging technique to clinical research. Methods: A co‐polarization system was developed where [1‐ 13 C]pyruvic acid (PA) and [ 13 C, 15 N2 ]urea in water solution were homogeneously mixed and polarized on a 5T SPINlab system. Physical and chemical characterizations and toxicology studies of the combined probe were performed. Simultaneous metabolic and perfusion imaging was performed on a 3T clinical MR scanner by alternatively applying a multi‐slice 2D spiral sequence for [1‐ 13 C]pyruvate and its downstream metabolites and a 3D balanced steady‐state free precession (bSSFP) sequence for [ 13 C, 15 N2 ]urea. Results: The combined PA/urea probe has a glass‐formation ability similar to neat PA and can generate nearly 40% liquid‐state 13 C polarization for both pyruvate and urea in 3‐4 h. A standard operating procedure for routine on‐site production was developed and validated to produce 40 mL injection product of approximately 150 mM pyruvate and 35 mM urea. The toxicology study demonstrated the safety profile of the combined probe. Dynamic metabolite‐specific imaging of [1‐ 13 C]pyruvate, [1‐ 13 C]lactate, [1‐ 13 C]alanine, and [ 13 C, 15 N2 ]urea was achieved with adequate spatial (2.6 mm × 2.6 mm) and temporal resolution (4.2 s), and urea images showed reduced off‐resonance artifacts due to the J CN coupling. Conclusion: The reported technical development and translational studies will lead to the first‐in‐human dual‐agent HP MRI study and mark the clinical translation of the first HP 13 C MRI probe after pyruvate.